Ectopic Fat Deposition on Insulin Sensitivity: Correlation of Hepatocellular Lipid Content and M Value - Beverly S. Hong; Ying Li; Shuiqing Lai; Juan Liu; Hongyu Guan; Weijian Ke; Xiaoying He; Yanbing Li (Journal of Diabetes Research)
Purpose. This study aimed to explore the relationship among insulin sensitivity and ectopic fat depots in participants with different glucose status. Methods. Fifty-nine men and women were enrolled in this study: 29 with normal glucose tolerance (NGT), 17 with impaired glucose tolerance (IGT), and 13 with type 2 diabetes mellitus (T2DM). All participants underwent a hyperinsulinemic-euglycemic clamp to assess the insulin sensitivity index (M value) and magnetic resonance imaging to measure the hepatocellular lipid content (HCL), skeletal muscle fat content including intramyocellular lipid (IMCL) and extramyocellular lipid (EMCL) of tibialis anterior (ta), and soleus muscle (sol). Results. The M value of NGT group was higher than those of IGT and T2DM groups (P=0.001). Participants with T2DM had the highest HCL and IMCL (ta) compared with those in NGT and IGT groups (P=0.001). The M value had an inverse relationship with HCL (r=-0.789, P=0.001), IMCL (sol) (r=-0.427, P=0.002), and IMCL (ta) (r=-0.419, P=0.002). Stepwise linear regression analysis showed that HCL (standardized β=-0.416; P=0.001) had an independent relationship with M value. Conclusions. Hepatocellular lipid content deposition happens earlier than skeletal muscle fat deposition. HCL is an independent risk factor for insulin resistance and may be used to evaluate the risk of developing T2DM as a noninvasive marker of insulin sensitivity index.